2019
DOI: 10.1016/j.msec.2019.109904
|View full text |Cite
|
Sign up to set email alerts
|

Blended alginate/collagen hydrogels promote neurogenesis and neuronal maturation

Abstract: Brain extracellular matrix (ECM) is complex, heterogeneous and often poorly replicated in traditional 2D cell culture systems. The development of more physiologically relevant 3D cell models capable of emulating the native ECM is of paramount importance for the study of human induced pluripotent stem cell (iPSC)-derived neurons. Due to its structural similarity with hyaluronic acid, a primary component of brain ECM, alginate is a potential biomaterial for 3D cell culture systems. However, a lack of cell adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 65 publications
(74 reference statements)
0
58
0
Order By: Relevance
“…These cells are very delicate, as previously evaluated from in vitro 2D cultures (Kyrousi et al, 2015). To this regard, we preferred to use a low viscosity bioink (Figure 3B), which will produce less shear stress, while in addition, it will reflect the brain matrix stiffness as several other studies have proposed (Crompton et al, 2007;Moxon et al, 2019;Distler et al, 2020). Following the bioprinting process, cultures were maintained in self-renewal conditions and subsequently were stained using antibodies recognizing Pax6, Sox2, GFAP, and Ki67.…”
Section: Self-renewal and Differentiation Potential Of Primary Derivementioning
confidence: 98%
“…These cells are very delicate, as previously evaluated from in vitro 2D cultures (Kyrousi et al, 2015). To this regard, we preferred to use a low viscosity bioink (Figure 3B), which will produce less shear stress, while in addition, it will reflect the brain matrix stiffness as several other studies have proposed (Crompton et al, 2007;Moxon et al, 2019;Distler et al, 2020). Following the bioprinting process, cultures were maintained in self-renewal conditions and subsequently were stained using antibodies recognizing Pax6, Sox2, GFAP, and Ki67.…”
Section: Self-renewal and Differentiation Potential Of Primary Derivementioning
confidence: 98%
“…Indeed, Her et al showed that mesenchymal stem cells can differentiate into the neuronal lineage in a substrate that present a Young modulus of 1 kPa, while they transformed into glial cells when this parameter is 10 kPa [ 124 ]. Moreover, a recent work has shown that the physicochemical properties of the alginate/collagen blend could resemble the ECM microenvironment, influencing neuronal-specific gene expression [ 125 ]. In particular, it was shown that oligodendrocyte differentiation and maturation in vitro is enhanced by substrates within the reported range of stiffness of the brain [ 126 ].…”
Section: Geometriesmentioning
confidence: 99%
“…This specific fabrication technique was used, and many phenotypic aspects were investigated, such as the analysis of neurite extension and neural maturation on polyethylene glycol [ 152 ] or 3-D gelatin methacrylate [ 153 ] hydrogels. Moreover, iPSC-derived mature neurons were bioprinted and cultivated on hydrogel scaffolds, and many read-outs were evaluated, such as the expression of integrins, the formation of a complex network, and the expression of synaptophysin along the neurites [ 125 ]. iPSCs can also be differentiated into glial cells, which proved to play a pivotal role in the pathogenesis of neurological disorders.…”
Section: Scaffolds For Neural Diseases’ Modelingmentioning
confidence: 99%
“…[300] Another approach to incorporating cell binding domains has been to mix in collagen fibrils, with this collagen/alginate blended hydrogel used to culture neurons generated from human iPSCs. [301] Other researchers have used defined mixtures of nutrients in agarose and alginate hydrogels to generate 3D multi-layered scaffolds that mimic cortical layers using primary rat cortical neurons in a microfluidic device. [302] Though the vast majority of neuronal tissue engineering has been achieved using rodent-derived neurons, combinatorial studies on matrix composition and architecture have sought to provide a more comprehensive understanding of how cellular microenvironment (ECM and signaling molecules) can influence cell fate in 3D cultures.…”
Section: Natural Hydrogel Systemsmentioning
confidence: 99%
“…[ 300 ] Another approach to incorporating cell binding domains has been to mix in collagen fibrils, with this collagen/alginate blended hydrogel used to culture neurons generated from human iPSCs. [ 301 ] Other researchers have used defined mixtures of nutrients in agarose and alginate hydrogels to generate 3D multi‐layered scaffolds that mimic cortical layers using primary rat cortical neurons in a microfluidic device. [ 302 ]…”
Section: Materials‐based Approaches To 3d Brain Modelsmentioning
confidence: 99%